Marketing Strategy To Increase Market Share In The Retail Industry - Chicilia Nova Yatna; Yulianah Yulianah (Jurnal Ekonomi, 2024)
In the face of increasingly fierce competition, retail companies need to implement innovative and adaptive marketing strategies to maintain and expand their market share. This research aims to examine effective marketing strategies in increasing market share in the retail industry. This research uses a descriptive method with a qualitative approach. The research results show that market share in the retail business is crucial for company dominance and competitiveness. Companies with a large market share can attract more consumers, increase sales, and gain an advantage in price negotiations with suppliers. The increase in market share reflects success in attracting customers, increasing operational efficiency, and strengthening the image and interest of investors. As a market leader, a company can control prices, lead market trends, and innovate for sustainable growth. Factors such as competitive pricing strategies, strategic store locations, quality products, superior customer service, and innovation influence market share. By integrating these strategies, companies can maintain strong market share in a competitive retail environment, increase customer loyalty, and create long-term growth.